WhiA transcription factor provides feedback loop between translation and energy production in a genome-reduced bacterium - Fisunov, Gleb Y.; Tsvetkov, Vladimir B.; Tsoy, Ekaterina A.; Evsyutina, Daria V.; Vedyaykin, Alexey D.; Garanina, Irina A.; Semashko, Tatiana A.; Manuvera, Valentin A.; Varizhuk, Anna M.; Kovalchuk, Sergey I.; Zubov, Alexander I.; Barinov, Nicolay A.; et al. (Frontiers in Microbiology, 2024)
IntroductionWhiA is a conserved protein found in numerous bacteria. It consists of an HTH DNA-binding domain linked with a homing endonuclease (HEN) domain. WhiA is one of the most conserved transcription factors in reduced bacteria of the class Mollicutes. Its function in Mollicutes is unknown, while it is well-characterized in Streptomyces. Here, we focused on WhiA protein from Mycoplasma gallisepticum.MethodsWe used a combination molecular dynamics, EMSA, MST and AFM to study the DNA-binding and ATP-binding properties of WhiA from M. gallisepticum. The transcriptional repressor function of WhiA was demonstrated using gene knockdown, reporter constructs and proteome analysis.ResultsWe demonstrate that WhiA homolog from M. gallisepticum binds a conserved sequence of the GAYACRCY core (Y = C or T, R = A or G), which is located in the promoter of an operon coding for ribosomal proteins and adenylate kinase (rpsJ operon). We show that WhiA in M. gallisepticum is a repressor of rpsJ operon and a sensor of ATP. HTH domain binds to the core motif and HEN domain binds to the auxiliary motif GTTGT that is located downstream to the core motif. We show that binding by both domains to DNA is required to fulfill the transcription repressor function. Knockdown of whiA does not affect actively growing M. gallisepticum, but leads to the growth retardation after freezing.DiscussionWe propose the following model for M. gallisepticum WhiA function. WhiA remains bound to the core motif at any conditions. At low ATP concentrations (starvation) HEN domain binds auxiliary motif and represses rpsJ operon transcription. At high ATP concentrations (nutrient-rich conditions) HEN domain binds ATP and releases auxiliary motif. It leads to the de-repression of rpsJ operon and increased production of ribosomal proteins.